2019
DOI: 10.3389/fpsyg.2019.01458
|View full text |Cite
|
Sign up to set email alerts
|

Pitch as the Main Determiner of Italian Lexical Stress Perception Across the Lifespan: Evidence From Typical Development and Dyslexia

Abstract: The study deals with the issue of lexical stress perception in both a developmental (comparing children and adults with typical development) and a clinical perspective (comparing typically developing children and children with dyslexia). The three parameters characterizing the acoustic profiles of words and non-words in a certain language are duration, pitch and intensity of its syllables. Based on (sparse) previous literature on Italian and other European languages, it was expected that syllable duration woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
2
3
0
Order By: Relevance
“…In terms of the effect size (ηp2), the group difference found in lexical tone awareness was the largest among all three types (ηp2 = 0.35, indicative of a “large” difference in the classification of Pierce, Block, & Aguinis, 2004), while the group differences in intonation and lexical stress were similar (ηp2= 0.12 and 0.10, both indicative of “medium” differences in the classification of Pierce et al, 2004). Generally, despite the structural differences, the lower performance in the three types of prosodic sensitivity in Chinese children with dyslexia found in our study echoed, to a certain extent, previous findings from alphabetic languages (e.g., Alves et al, 2015; Caccia et al, 2019; Goswami et al, 2010; Hazan et al, 2013; Ziegler et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In terms of the effect size (ηp2), the group difference found in lexical tone awareness was the largest among all three types (ηp2 = 0.35, indicative of a “large” difference in the classification of Pierce, Block, & Aguinis, 2004), while the group differences in intonation and lexical stress were similar (ηp2= 0.12 and 0.10, both indicative of “medium” differences in the classification of Pierce et al, 2004). Generally, despite the structural differences, the lower performance in the three types of prosodic sensitivity in Chinese children with dyslexia found in our study echoed, to a certain extent, previous findings from alphabetic languages (e.g., Alves et al, 2015; Caccia et al, 2019; Goswami et al, 2010; Hazan et al, 2013; Ziegler et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, Hazan, Messaoud-Galusi, and Rosen (2013) reported that dyslexic children had significantly less sensitive to various stimuli containing multiple intonation patterns (i.e., rising, falling, steady or rising-falling) than typically developing children. This view has been further validated by other studies that also focused on relevant sensory abilities, such as pitch perception (e.g., Caccia et al, 2019;Ziegler, Pech-Georgel, George, & Foxton, 2012). Such insensitivity in intonation awareness in children with dyslexia was found to be transferred to influent intonation in their oral expression (Alves, Reis, & Pinheiro, 2015).…”
Section: Lower Prosodic Sensitivity Of Children With Dyslexiasupporting
confidence: 63%
See 1 more Smart Citation
“…To this aim, further research is needed to better understand the relationships and mutual influences between language and rhythm perception in these populations, and to define the developmental trajectories of such relationships. Moreover, further studies are needed to shed light on the processing of the single acoustic parameters (duration, pitch, and intensity) in children with DD and DLD (see also Caccia et al., 2019). In an intervention‐oriented perspective, prosodic tasks specifically designed to address segmental or suprasegmental analysis could be useful tools for the prevention and rehabilitation of DLD in the clinical practice, since they are enjoyable and motivating tasks that can easily be delivered in the form of games (e.g., dee‐dee—analogous tasks, prosody imitation, sentence–picture matching tasks etc.).…”
Section: Discussionmentioning
confidence: 99%
“…A smaller proportion of polysyllabic words are stressed on the antepenultimate syllable. Stress Position has been found to modulate the effect of the parameters determining lexical accent perception in TD children, but marginally so in children with DD (see Caccia et al., 2019).…”
Section: Introductionmentioning
confidence: 99%